Nursing before Nightingale, 1815-1899 - Helmstadter, Carol; Godden, Judith (Farnham, Surrey, England ; Burlington, VT : Ashgate Pub., 2011)
Nursing Before Nightingale is a study of the transformation of nursing in England from the beginning of the nineteenth century until the emergence of the Nightingale nurse as the standard model in the 1890s. From the nineteenth century on historians have considered Florence Nightingale, with her training school established at St. Thomas's Hospital in 1860, the founder of modern nursing. This book investigates two major earlier reforms in nursing: a doctor-driven reform which came to be called the 'ward system, ' and the reforms of the Anglican Sisters, known as the 'central system' of nursing.
The new medicine and its dependence on good nursing -- Hospital nursing in the first part of the century -- The ward system: a doctor-driven reform -- Early efforts at training -- Nursing at the crossroads, part I: ladies and religious sisters in the Crimean war -- Nursing at the crossroads, part 2: working-class nurses in the Crimean War -- St John's House and its mission -- The St John's House central nursing system -- The demise of sisterhood nursing and the central system.
Includes bibliographical references (p. [197]-209) and index.
Keywords: Nursing -- Great Britain -- History -- 19th century